Novel retinoblastoma mutation abrogating the interaction to E2F2/3, but not E2F1, led to selective suppression of thyroid tumors. Issue 10 (29th September 2014) - Toki, Hideaki; Inoue, Maki; Minowa, Osamu; Motegi, Hiromi; Saiki, Yuriko; Wakana, Shigeharu; Masuya, Hiroshi; Gondo, Yoichi; Shiroishi, Toshihiko; Yao, Ryoji; Noda, Tetsuo
<x xml:space="preserve">Abstract</x> Mutant mouse models are indispensable tools for clarifying gene functions and elucidating the pathogenic mechanisms of human diseases. Here, we describe novel cancer models bearing point mutations in the retinoblastoma gene (Rb1) generated by N‐ethyl‐N‐nitrosourea mutagenesis. Two mutations in splice sites reduced Rb1 expression and led to a tumor spectrum and incidence similar to those observed in the conventional Rb1 knockout mice. The missense mutant, Rb1D326V/+, developed pituitary tumors, but thyroid tumors were completely suppressed. Immunohistochemical analyses of thyroid tissue revealed that E2F1, but not E2F2/3, was selectively inactivated, indicating that the mutant Rb protein (pRb) suppressed thyroid tumors by inactivating E2F1. Interestingly, Rb1D326V/+ mice developed pituitary tumors that originated from the intermediate lobe of the pituitary, despite selective inactivation of E2F1. Furthermore, in the anterior lobe of the pituitary, other E2F were also inactivated. These observations show that pRb mediates the inactivation of E2F function and its contribution to tumorigenesis is highly dependent on the cell type. Last, by using a reconstitution assay of synthesized proteins, we showed that the D326V missense pRb bound to E2F1 but failed to interact with E2F2/3. These results reveal the effect of the pRb N‐terminal domain on E2F function and the impact of the protein on tumorigenesis. Thus, this mutant mouse model can be used to investigate human Rb family‐bearing mutations at the N‐terminal region.